Новые виды пчел рода Andrena (Hymenoptera, Andrenidae) из Таджикистана - Осычнюк, A.3. (Вестник зоологии, 1982)
Two species of Andrena (Poecilandrena)a r edescribed as new. A. (P.) segregata sp. n.--- similar to A. saturata W a r. and A. kilikiae War.; female si distinct by the
s h a p e of ocular fissures, mesonotal and tergal sculpture, pale pubescensetc.; male differs by the sizeof second antennal segment and genitalstructures. A.(P.) kondarensis sp. n.- - female ditters from closely related A. rusticola W a r . by the shape of labral
process, coarse clypeal sculpture, mesonotal sculpture etc.; male ditters irom closely related A. viridescens DU
Vier, the size of the third-fourth segments or the antennal, genital Structures, sculptures, colouration, etc.